2015
DOI: 10.2169/internalmedicine.54.2997
|View full text |Cite
|
Sign up to set email alerts
|

The Serum Lipids Levels may be Underestimated in Patients on Hemodialysis

Abstract: Objective Although lipid disorders are a well-known risk factor for cardiovascular disease (CVD) in the general population, the optimal management with lipid-lowering therapy to reduce CVD risks and mortality in hemodialysis (HD) patients remains controversial. In the clinical setting, dyslipidemia can be diagnosed based on the detection of elevated lipid concentrations at the beginning of HD. This study investigated changes in the levels of serum lipids during a single HD session. Methods The serum total chol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The evaluation of lipids in the pre-dialysis serum may underestimate the true lipemic levels, since before the hemodialysis (HD) sessions the individuals have greater weight (due to a greater amount of free water), impairing results and hindering therapeutic management 24 . In this study, we did not identify prePTx elevated lipids and justified the increase in LDLcholesterol after surgery by other factors, other than nutritional or metabolic, such as oxidative stress, inflammation and possible endothelial dysfunction, as described by Nitta 25 .…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of lipids in the pre-dialysis serum may underestimate the true lipemic levels, since before the hemodialysis (HD) sessions the individuals have greater weight (due to a greater amount of free water), impairing results and hindering therapeutic management 24 . In this study, we did not identify prePTx elevated lipids and justified the increase in LDLcholesterol after surgery by other factors, other than nutritional or metabolic, such as oxidative stress, inflammation and possible endothelial dysfunction, as described by Nitta 25 .…”
Section: Discussionmentioning
confidence: 99%
“…However, genetic, ethnic, and racial factors, as well as the HD treatment and the ultrafiltration rate, can affect serum lipids and therefore patients' outcomes. 19,20 Predialysis serum creatinine concentration has been suggested as an indirect measure of muscle mass in HD patients and the International Society of Renal Nutrition and Metabolism (ISRNM) includes this parameter in the diagnostic criteria for PEW. In our study, we observed lower serum creatinine and CI in the group of patients with BCMI <6.4 kg/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…However, there are different factors that can affect serum lipids and therefore patient outcomes. The factors that have been described are genetic, ethnic and racial factors as well as the HD treatment per se and the ultrafiltration rate (Moradi et al ; Ueno et al ).…”
Section: Limitations Of the Studymentioning
confidence: 99%